Integrating Ideological-Political Education in Educational Psychology: A Psychological Education Perspective - liu, lixia (Pacific International Journal, 2026)
Addressing the imperative to deeply integrate "cultivating virtue and nurturing talent" into higher education, this study investigates a teaching reform model for the Educational Psychology course. The reform is designed to overcome common pitfalls of superficial Ideological and Political Education (IPE) integration by utilizing the perspective of psychological education as its foundational conduit. Grounded in theories of Self-Determination and constructivist learning, the model proposes a synergistic integration where psychological education principles create the supportive conditions for the internalization of professional values and ethics. The implementation involves a four-pillar strategy: restructuring course content into thematic, value-integrated modules; adopting experiential and dialogic teaching methods; embedding praxis-oriented practical components; and instituting a multi-modal, process-oriented assessment system. A multi-dimensional evaluation of the reform’s effectiveness, based on classroom observations, student reflections, and process assessments, indicates significant positive outcomes. These include a marked transformation in student engagement towards active, critical participation, enhanced psychological literacy and self-regulatory capacity, the construction of a values-informed professional identity, and improved competence in translating theory into ethically sound practice. The study concludes that psychological education provides a powerful and necessary framework for achieving authentic, student-centered IPE integration within professional curricula. It offers a replicable pedagogical model that contributes to the holistic development of future educators, equipping them with both professional expertise and a strong ethical foundation. Limitations concerning faculty development and practical scalability are noted, pointing to directions for future refinement and research.